The art of beef cutting : a meat professional's guide to butchering and merchandising - Underly, Kari (Wiley, 2011)
"The Art of Beef Cutting is the only book on the market that combines a complete listing of beef cuts, including full-color photos and NAMP/IMPS numbers for each cut, with step-by-step instructions on basic meat cutting techniques"-- Provided by publisher